Prophylactic use of antibiotic laden poly methyl methacrylate beads in the management of open fractures: a novel approach for control of orthopaedic infection - Seenappa, Hariprasad; Patil, Prabhulingreddy; Madamanchi, Harsha; Sivanandan, Sakthikesavan (International Journal of Research in Orthopaedics, 2019)
Background: Control of infection in open fractures is a challenge in orthopaedic surgery. The literature provides evidence that antibiotic-laden bead chains are a useful adjuvant with systemic antibiotics in the prevention of infection in open fractures. Methods: Between February 2018 and January 2019, sixty four patients with open type fractures admitted in emergency room were analysed for this study. In this 64 patients, 32 in Group A received antibiotic laden PMMA (Poly methyl methacrylate) beads with standard care. Another 32 in Group B received standard care. Results: There were 54 males and 10 females with a mean age of 41 and follow up 6 months. Among 64 patients 37 patients were stabilised with external fixators and remaining 17 patients underwent a definitive fixation either an intramedullary nailing (12 patients) or internal fixation with a plate (5 patients). 10 patients were stabilised with k wires. The infection rate in group A and B was 6.25% and 21.8% respectively which is statistically not significant (p=0.072). Conclusions: Although the final infection control rate was comparable between the bead group (30/32, 93.75%) and the non bead group (25/32, 78.12%), few complications were noted in the bead group (9.37%, 3/32) than in the group B (15.62%, 5/32). Hence the prophylactic use of antibiotic cement beads is advantageous in preventing post traumatic orthopaedic infection, lessens hospital stay as well the financial burden to the patients.